The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/jima-07-2020-0211
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality to organizational citizenship behavior from Islamic perspective: mediating role of spirituality at work and organizational commitment

Abstract: Purpose This study aims to determine the direct and indirect effects of Islamic spirituality on organizational citizenship behavior (OCB) Islamic perspective (OCBIP), identifying the role of spiritual and marketing strategy at work and organizational commitment to mediate the effect of Islamic spirituality on OCBIP. Design/methodology/approach The research population is all employees of Sidoarjo BRI Syari'ah Branch Office. Total sample involves 130 fulltime employees. Proportional random sampling technique i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 67 publications
2
9
0
1
Order By: Relevance
“…Research showed that effective leadership boosts employees' productivity and job satisfaction by improving their motivation (Goleman, 2002;Locke and Latham, 1990;Petty et al, 1984;Kouzes and Posner, 2002). Some studies predicted a strong link between effective leadership and work satisfaction (Podsakoff et al, 1990(Podsakoff et al, , 1996Walumbwa, 2002;Chen, 2005aChen, , 2005bMadlock, 2008;Parkinson, 2008;Temple, 2009;Ed u Valsania et al, 2012;Tonkin, 2013;Muhdar and Rahma, 2015;Sani et al, 2018). Thus, the present study proposes the following hypothesis: H1.…”
Section: Literature Review 21 Effective Leadership and Job Satisfactionmentioning
confidence: 68%
See 2 more Smart Citations
“…Research showed that effective leadership boosts employees' productivity and job satisfaction by improving their motivation (Goleman, 2002;Locke and Latham, 1990;Petty et al, 1984;Kouzes and Posner, 2002). Some studies predicted a strong link between effective leadership and work satisfaction (Podsakoff et al, 1990(Podsakoff et al, , 1996Walumbwa, 2002;Chen, 2005aChen, , 2005bMadlock, 2008;Parkinson, 2008;Temple, 2009;Ed u Valsania et al, 2012;Tonkin, 2013;Muhdar and Rahma, 2015;Sani et al, 2018). Thus, the present study proposes the following hypothesis: H1.…”
Section: Literature Review 21 Effective Leadership and Job Satisfactionmentioning
confidence: 68%
“…More and more studies have focused on the effectiveness of leadership and how it affects a variety of outcomes during the last decade. Effective leadership has a big impact on how employees behave in terms of organisational citizenship responsibility (Rodrigues and Ferreira, 2015;Sarwar et al, 2015;Ismaeelzadeh et al, 2016;Saif et al, 2016;Cofie, 2018;Hassi, 2018) and demonstrate job satisfaction (Ogbonna and Harris, 2000;Podsakoff et al, 2000;Ed u Valsania et al, 2012;Muhdar and Rahma, 2015;Sani et al, 2018). Employees often go above and beyond their job descriptions when they work under effective leadership (OCB, 2018).…”
Section: Effective Leadership Job Satisfaction and Organisational Cit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that OCB affects organizational performance such as financial performance, compliance, job satisfaction, cultural value, and innovative service performance (Fry & Cohen, 2009;Marinova et al, 2010;Sidin et al, 2020;Wu et al, 2023), Employee turnover (Chen et al, 1998), commitment (Brief & Motowidlo, 1986;Sani & Ekowati, 2022), job satisfaction (Dubey et al, 2022;Organ, 1997), and employee performance (Nurrohmat, 2022;Sani & Ekowati, 2019) Islamic OCB is the awareness that a Muslim has to do something more for his organization, not just work according to the job description. Employees try to contribute to the progress of the organization in a voluntary way because Islam encourages its people to act sincerely for the common interest.…”
Section: Islamic Organizational Citizenship Behaviormentioning
confidence: 99%
“…Effective companies can be identified by the intensity of interaction among employees, groups, and the organizational system to obtain employee performance with low absenteeism rates, low labor turnover, minimal 15,2 deviant behavior within the organization, job satisfaction, commitment to the company, and also organizational citizenship behavior. Workers are certainly important assets in an organization, playing an extra role in the workplace in their behavior more than their job description, called Organizational Citizenship Behavior (OCB), which will determine a good level of performance (Belwalkar et al, 2018;Nurrohmat, 2022;Ocampo et al, 2018;Organ, 1997;Sani & Ekowati, 2022;Wu et al, 2023). Particularly, the characteristic of organizational members with OCB is that they are oriented towards innovative performance, so it can directly impact the survival and improvement of organizational performance in a competitive environment to remain superior.…”
Section: Introductionmentioning
confidence: 99%